3(2x-4)=5(-3x+6)

Simple and best practice solution for 3(2x-4)=5(-3x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-4)=5(-3x+6) equation:



3(2x-4)=5(-3x+6)
We move all terms to the left:
3(2x-4)-(5(-3x+6))=0
We multiply parentheses
6x-(5(-3x+6))-12=0
We calculate terms in parentheses: -(5(-3x+6)), so:
5(-3x+6)
We multiply parentheses
-15x+30
Back to the equation:
-(-15x+30)
We get rid of parentheses
6x+15x-30-12=0
We add all the numbers together, and all the variables
21x-42=0
We move all terms containing x to the left, all other terms to the right
21x=42
x=42/21
x=2

See similar equations:

| 32x-4=5-3x+6 | | x=(4x-3)+(2x+11) | | 3x+1/4-3=5x-4/3 | | 2.4/x=3/4.5 | | X+.07x=97.26 | | 7x+7=11x-25 | | 7x+7=(11x-25) | | (7x+7)=(11x-25) | | 3(2x-4)=-5(x-2) | | 2x-(3x-4)=11 | | 5t=-3=2t+5 | | 6x(5)+4+1(6)=2x-3(10) | | 4m^2+5m+7=0 | | 2a-48=5a | | s/6.2s+14.18=–37.28 | | -1-22n=-20-9 | | x(3x-5)(2x-19)=180 | | 20n(n+2)=9n-12 | | x+(5x+19)+x=180 | | -5+31=-14n-5 | | 7^x=(1/49)^(x+3) | | 6=12-x/3 | | -4x+(-9)x+19=15+10 | | 102=1.2•w | | 3x+x+75=180 | | -4=8-2/3*x | | T(n)=2(n+1) | | 2x+x=+10+11 | | 300=51•p | | -4=8-2/3x | | 5z-2=28 | | -x/4+5=9 |

Equations solver categories